Religiosidad femenina y herejía: monjas y beatas «luteranas» ante la Inquisición de Sevilla en tiempos del Emperador. - BOEGLIN, MICHEL (Scripta, 2016)
During the repression of Lutherian heresy in Seville (1557-1565), women represented a signiicant percentage of the convicted. And among the persons sentenced to death, women played a central role in the spread of the new doctrines. We will focus more particularly on the case of religious and «beatas» judged on that occasion.